Analysis of Antioxidant Enzyme Activity and Antioxidant Genes Expression Dur ing Germination of Two Different Genotypes of Lolium multiflorum Under Salt Tolerance - Wang, Xia; Ma, Xiao; Xinquan-Zhang; Linkai-Huang; Li, Zhou; Gang Nie, Wenzhi-Xu (Protein and Peptide Letters, 2016)
Annual ryegrass (Lolium multiflorum) is widely used as a cool-season forage grass for its luxuriant growth, palatable and high digestible. To investigate the salt tolerance mechanism in annual ryegrass under salt stress, salt-tolerant genotype ‘R102-3’ and salt-sensitive genotype ‘Tetragold’ were subject to 300mmol/L NaCl in a controlled growth chamber for 12 days. The results showed high concentrations of NaCl decreased relative water content (RWC), and increased the electrolyte leakage (EL) in both genotypes. However the ‘Tetragold’ had a greater increased extent of malondialdehyde (MDA) and EL than in ‘R102-3’, in contrast, the activities of Superoxide (SOD), Peroxidase (POD), Catalase (CAT) and Ascorbate peroxidase (APX) were higher in salt resistant compared to sensitive ones. For ensure the accurate of qRT-PCR, we used RefFinder to choose the most stably reference genes eEF1A(s) and GAPDH to normalize the antioxidant genes expression data. The results indicated that higher expression of Fe-SOD, Mn-SOD, Chl-Cu/Zn SOD, Cyt-Cu/Zn SOD, POD and CAT in ‘R102-3’ when compared with ‘Tetragold’, which may play an important role in defensed damage of Reactive oxygen species (ROS) under salt stress. Thus, the salt-tolerant genotype could effectively resist oxidative damage induced by salt tress relative to salt-sensitive genotype.
Keywords: genes expression